Drainage pattern and its distribution in the Kathmandu valley - Bajracharya, S. R. (Journal of Nepal Geological Society, 1991)
Drainages in the Kathmandu Valley traverse the hills made up of metasedimentary rocks and Sheopuri Injection Gneiss, and the plains of fluvio-lacustrine sediments. As the streams cut into the underlying rocks and structures of the region, they give rise to certain drainage arrangement seven types of drainage patterns are identified in the valley. They are Dendritic, Rectangular, Trellis, Sub-parallel, Barbed, Radial and Centripetal. The Kathmandu Valley as a whole is a centripetal drainage pattern and the other drainage patterns are distributed in different tributaries within the valley.